2014
DOI: 10.1186/1471-2458-14-1185
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for cervical neoplasia: a cervical cancer screening program in Beijing

Abstract: BackgroundCervical cancer is the second most common cancer and cause of cancer-related death for women worldwide. The aims of this study were to investigate the prevalence of cervical neoplasia and examine factors associated with high-grade cervical squamous intraepithelial lesions (HSIL) among women taking part in a cervical cancer screening program in Beijing.MethodsWomen aged 25–65 years were screened using the ThinPrep cytologic test and gynecologic examination. Univariate and multivariate logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
2
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 41 publications
7
58
2
8
Order By: Relevance
“…The finding of this study reveals that multiple sexual partners are significantly associated with cervical cancer as compared to those women who have no exposure of multiple sexual partners (AOR=40; 95% CI: 22.44,70.204) and having history of STI exposure and being HIV positive became significant with the outcome variable of the study as compared to those women who have no history of STI exposure and HIV negative (AOR=8.3 :95%CI: 5.639,12.405) and (AOR=9:95% CI: 9:4.537,17.985) respectively. This is similar with the study that has been conducted on cervical cancer screening program in Beijing [32]. A study in Zambia among HIV infected women states that HIV positive women have higher likelihood of having high grade cervical squamous intra epithelial lesion (AOR=8.0 :95% CI: 20.54,52.04) and cervical cancer cases are reported to occur in more in the immune suppressed cases [4].…”
Section: Discussionsupporting
confidence: 85%
“…The finding of this study reveals that multiple sexual partners are significantly associated with cervical cancer as compared to those women who have no exposure of multiple sexual partners (AOR=40; 95% CI: 22.44,70.204) and having history of STI exposure and being HIV positive became significant with the outcome variable of the study as compared to those women who have no history of STI exposure and HIV negative (AOR=8.3 :95%CI: 5.639,12.405) and (AOR=9:95% CI: 9:4.537,17.985) respectively. This is similar with the study that has been conducted on cervical cancer screening program in Beijing [32]. A study in Zambia among HIV infected women states that HIV positive women have higher likelihood of having high grade cervical squamous intra epithelial lesion (AOR=8.0 :95% CI: 20.54,52.04) and cervical cancer cases are reported to occur in more in the immune suppressed cases [4].…”
Section: Discussionsupporting
confidence: 85%
“…Também utilizando resultados de citologia oncótica, recente estudo chinês encontrou prevalência de 0,12% de lesões precursoras do câncer cervical em 728.704 mulheres 13 . Estudo randomizado com 41.955 mulheres com mais de 25 anos encontrou prevalência de alteração na citologia oncótica de 6%, que poderia ser decorrente de células escamosas atípicas de significado indeterminado (ASCUS) ou HSIL.…”
Section: Métodosunclassified
“…Majority 87.17% of the patients in our study were from the rural area, but this is in contrast to the China Cancer Registration Annual Report 2004, in which 43 cancer registries were included, the incidence of cervical cancer was 5.3 per 100,000 in urban and 4.9 per 100,000 in rural areas. 11 Similar to the present study, the incidence of high-grade lesion for cervical cancer was found to be high among the rural population and they were susceptible to develop the cancer as shown in the study by Parimala A et al 12 High education level (college and above compared with junior middle school or lower) was found to be protective for HSIL (aOR = 0.79, 95% CI: 0.37-0.90) in the study by Lixin Tao et al 13 60% of the women were house wives in the study done by Niveditha VS et al while in the present study, 87.7% were house wives.…”
Section: Discussionmentioning
confidence: 88%